Patients’ Perception on Clinical Training and Informed Consent Towards Medical Students in Jazan Hospitals: A Cross-Sectional Study - Alharbi, Ahmad A.; Alhazmi, Abdulaziz; Jaawna, Essa; Zogel, Basem; Hakami, Faisal; Abusageah, Faisal; Hakami, Khalid M.; Khawaji, Meshal; Hakami, Alwaleed; Refaei, Eman; Abdulwali, Hany M.; Hakami, Mohammed; et al. (International Journal of Statistics in Medical Research, 2024)
Background: Bedside teaching offers many advantages for medical education. When real patients are involved in the clinical practice, teaching medicine often involves difficult ethical dilemmas so it must be precisely detected and properly dealt with. Objective: to evaluate patients' perspectives on clinical training and informed consent within teaching hospitals in Jazan. Method: This cross-sectional observational study targeted all adult who previously met a medical student. A self-administered questionnaire to assess the patient’s perspective on clinical training and informed consent towards medical students were answered by the participants. T-tests and chi-square tests, along with multiple logistic regression, were used for analysis. Results: 200 participants were selected for this study with a mean age of 32.52 years. 51.3% of the participants were female, and 55.3% of the participants were married. 59.6% of the patients reported that the doctor asked for their permission for the student to be present. Only 31.1 % stated that they felt uncomfortable and 70% of the participants reported that they received more explanation about their illness when medical students were present. Almost all patients felt pleased that they had contributed to the students’ medical education. Conclusion: The research has demonstrated that patients' acceptability of medical students appeared to be influenced by the nature of the interaction between the patient and the student, the education level, and the student-patient gender. In general, most patients were pleased that they were able to help in the students' medical education. In order to enhance the learning process for medical students, clinical tutors must benefit from patients who accept medical students.